Does Unpaid Care Work affect the Well-being of Care Providers? Evidence from Kerala, India - Anila Skariah (Asian Journal of Research in Social Sciences and Humanities, 2014)
In most countries the provision of care in the family continues to lie unbalanced mainly with women on an unpaid basis. Unpaid care work has multidimensional aspects of well-being which can have many positive benefits from the care received and also have costs for those who provide care. This paper examines the implications of unpaid care work on human well-being in the Madapally panchayat of Kerala state of India. The study makes use of is a small scale exploratory design utilizing cross-sectional face to face recall interview schedule and focus group discussions from 315 households. Factor analysis was done for each group to extract the most significant factors that are related to well-being of the care providers. It is found that there exist gender differences in factors that negatively affect well-being of care providers. The study shed light on the need for gender budgeting